Reframing ecological ethics through green literature: An interdisciplinary ecocritical perspective - Rosani, Gita (Journal of Critical Ecology, 2026)
Background: This article discusses green studies literature in general. A specific analysis of green studies in Antoine de Saint-Exupéry's novella, Le Petit Prince, with the theory of ecocriticism. For nowadays, humans should have a high level of respect for nature. Nature is a provider that must be respected and protected, one way to do this is through green studies literature. Unfortunately, the results of this study are limited to that point and do not examine green studies comprehensively. Methods: This study employed a literature review with content analysis of secondary data, then presented narratively. The theories employed include ecocriticism, ecolinguistics, ecodramaturgy, and the anthropocene. The online language translation tool, Google Translate, was used. Google Docs was used for grammar correction. Findings: These findings indicate that green studies has been shown to raise human awareness to restore the balance of nature so that future generations can still enjoy it. Through language as a means of conveying messages. Green literature always gives people space to breathe, think clearly, and act wisely so that environmental destruction does not occur. Even if nature has been damaged, through the study of green literature and interdisciplinary studies, efforts to heal nature are possible. This is in line with changing human thought patterns and actions. Ultimately, to restore balance to the universe, humans, as movers and users, must first restore their own balance and eliminate all greed and all acts of violence, no matter how small. Conclusion: Green Literature emphasizes human responsibility toward nature by fostering ecological awareness, ethical reflection, and intergenerational justice through language and literary expression, positioning ecolinguistics and narrative forms—both verbal and nonverbal—as powerful tools to interpret environmental realities, critique exploitative power, and inspire collective action to protect and restore the earth sustainably. Novelty/Originality of this article: This article offers an original interdisciplinary contribution to ecological discourse by situating literary analysis within broader green studies frameworks and connecting narrative ethics to contemporary environmental challenges.